Information Value in Social Media: An Integrated Approach to Preventive Behaviors under COVID-19 - Cu, Le Xuan (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 1 No 3, 2021)
Information content via social media has received attention from the community during the pandemic. This work aims to examine a preventive behavior model due to information value through social media under COVID-19 in Vietnam. This model is formulated based on the integration of Health Belief Theory (HBT) and the Elaboration Likelihood Model (ELM). A web-based survey is performed to collect data from 321 respondents who have utilized social media to seek and accumulate COVID-19-related information. The results indicate that perceived threat and self-efficacy are two vital predictors of readiness to uptake preventative behaviors. Additionally, information dimensions (i.e., information quality and information credibility) are crucial motivations underlying perceived threat and self-efficacy. Information quality well surmises information credibility. Finally, theoretical and practical implications are discussed.